Effect of dried leaves of Leucaena leucocephala on rumen fermentation, rumen microbial population, and enteric methane production in crossbred heifers - Montoya Flores, María Denisse; Molina Botero, Isabel Cristina; Arango, Jacobo; Romano Muñoz, José Luis; Solorio-Sánchez, Francisco Javier; Aguilar-Pérez, Carlos Fernando; Ku-Vera, Juan Carlos (MDPI, 2020)
The effects of dietary inclusion of dried Leucaena leucocephala leaves (DLL) on nutrient digestibility, fermentation parameters, microbial rumen population, and production of enteric methane (CH4) in crossbred heifers were evaluated. Four heifers were used in a 4 × 4 Latin square design consisting of four periods and four levels of inclusion of DLL: 0%, 12%, 24%, and 36% of dry matter (DM) intake. Results showed that DM intake (DMI), organic matter intake, and gross energy intake (GEI) were similar (p > 0.05) among treatments. Apparent digestibility of organic matter, neutral detergent fiber, and energy decreased with increasing levels of DLL in the ration (p < 0.05). In contrast, digestible crude protein (CP) was higher (p < 0.05) in treatments with 12% and 24% DM of DLL. The inclusion of DLL did not affect (p > 0.05) rumen pH and total volatile fatty acids. Rumen microbial community was not affected (p > 0.05) by treatment. There was a linear reduction (p < 0.05) in CH4 emissions as the levels of DLL in the ration were increased. Results of this study suggest that an inclusion of 12% DM of ration as DLL enhances digestible CP and reduces daily production of enteric CH4 without adversely affecting DMI, rumen microbial population, and fermentation parameters.